2011
DOI: 10.1111/j.1469-7610.2011.02499.x
|View full text |Cite
|
Sign up to set email alerts
|

Empathy in children with autism and conduct disorder: group‐specific profiles and developmental aspects

Abstract: In this study, distinct empathic profiles in children with ASD and CD-CU+ were found. Furthermore, the work demonstrates improvement of empathic skills throughout childhood and adolescence, which is comparable for individuals with psychiatric disorders and control children. These results yield implications for further research as well as for therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
185
7
7

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(246 citation statements)
references
References 39 publications
27
185
7
7
Order By: Relevance
“…Finally, the BES-C could prove useful for studying empathy from a new perspective, particularly in children who display impaired empathy, such as those with autism spectrum disorder (e.g., Bons et al, 2013;Schwenck et al, 2012). This would extend the current literature on empathy in middle childhood.…”
Section: Discussionmentioning
confidence: 89%
“…Finally, the BES-C could prove useful for studying empathy from a new perspective, particularly in children who display impaired empathy, such as those with autism spectrum disorder (e.g., Bons et al, 2013;Schwenck et al, 2012). This would extend the current literature on empathy in middle childhood.…”
Section: Discussionmentioning
confidence: 89%
“…Early research suggested empathy impairments were characteristic of ASD based on ToM limitations (Baron-Cohen 1995; see Yirmiya et al 1998, for a review), but more recent research indicates more nuanced empathic strengths and challenges in ASD (Senland and Higgins-D'Alessandro 2013;Rueda et al 2015). ToM, often used interchangeably with cognitive empathy in ASD studies (Schwenck et al 2012;Rueda et al 2015), refers to the capacity to interpret others' mental states, such as their intentions, feelings, and wants (Baron-Cohen 1995). While children and adults with high functioning ASD can often pass basic ToM tasks (Bowler 1992;Dahlgren and Trillingsgaard 1996), they often, but not always (Begeer et al 2010;Scheeren et al 2013), experience impairments on advanced and naturalistic ToM tasks that assess more subtle ToM difficulties in comprehending intentions when people say things they do not mean (Schwenck et al 2012), interpreting animated stimuli interacting in ways that suggest intentionality (Jones et al 2010), or understanding intentions, deception, and sarcasm in videos of conversations (Mathersul et al 2013).…”
mentioning
confidence: 97%
“…This study took a multidimensional approach to empathy, considering cognitive and affective empathy as distinct capacities (Davis 1983;Rogers et al 2007;Rueda et al 2015;Schwenck et al 2012). Davis' (1983) terminology is used; thus, cognitive empathy refers to perspective-taking; affective empathy refers to empathic concern and to personal distress.…”
mentioning
confidence: 99%
“…Deficits in social cognition, e.g., inferring others' mental states such as emotions and perspective taking, are at the core of the disorder [2,3,4]. Socioemotional functions such as empathic feelings (being emotionally affected by someone else's emotions) have also been suggested to be aberrant, though less consistently [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%